Migrant Workers and the Process of Criminalization : An Analysis of Offense Patterns and Spatial Dimensions in Thailand - Charoensuk, Khotchatrai; Kesorn, Charin (Journal of Thai Ombudsman, 2026)
This article aims to explain how migrant workers are criminalized through state governance mechanisms at the local level in migrant-dense areas of Thailand. The analysis draws on secondary data from laws, policy documents, previous studies, and statistics on migrant prisoners in five provinces: Samut Sakhon, Samut Prakan, Samut Songkhram, Ratchaburi, and Nakhon Pathom. The findings show a total of 853 detained migrant workers, with Myanmar nationals constituting the largest share (675 persons, 79.10%). Ratchaburi recorded a particularly high rate of 91.20 migrant prisoners per 10,000 migrant workers. The study finds that the state brings migrant workers into a condition of criminality through three key mechanisms: the use of laws and penalties to regulate legal status and employment; local-level law enforcement through inspection, arrest, detention, and deportation; and security discourses that frame migrant workers as risk groups or outsiders rather than as contributors to the economy. In terms of case structure, three major categories were identified: offences against life and bodily integrity, documentation-related offences, and drug-related offences, respectively. Differences in offence types across provinces indicate that migrant workers’ entry into the criminal justice process is not determined solely by their individual behavior, but is also related to documentation regimes, the discretion of officials, and localized forms of regulation and control. The high proportion of documentation-related offences in Samut Sakhon and Nakhon Pathom reflects the role of documentation regimes and variations in law enforcement practices across provinces. This article therefore argues that policy design should reduce the tendency to push problems of legal status and documentation into the criminal justice process. It should also strengthen good governance in law enforcement through fair standards of discretion and develop accessible systems for registration and status maintenance that reduce the costs of entering the formal system and the incentives for falling out of it. Such an approach would enable migrant labor governance to create sustainable order based on a balance between economic needs, security concerns, and the rights of migrant workers.